Polymorphonuclear leukocyte migration through human amnion membrane - Russo, RG (The Rockefeller University Press, 1981)
A new in vitro model has been developed for studying migration of human polymorphonuclear leukocytes (PMN) through living native cellular and matrix barriers. Human amnion membrane consists of a single layer of epithelium bound to a continuous basement membrane interfacing an avascular collagenous stroma. Living amnion was placed in plastic chambers with separate compartments on each side of the membrane. PMN were introduced on the epithelial side of the amnion, and a Millipore filter (Millipore Corp., Bedford, Mass.) was placed against the stromal side. In response to N-formylmethionyl-leucyl- phenylanlanine (FMLP) chemoattractant, PMN penetrated the full thickness of the amnion and were collected and counted on the filter. The rate of PMN traversal of the amnion was dependent on the concentration of FMLP (optimal at 10(-8)M) as well as the slope of the FMLP gradient across the amnion. The route of PMN migration was studied by transmission electron microscopy. PMN first attached to the epithelial surface, then infiltrated between intercellular junctions. PMN migrated around or through tight junction and hemidesmosome attachments. The PMN then penetrated the basement membrane and migrated through the dense collagenous stroma. The present amnion migration system has characteristics of the in vivo inflammatory state not described in any previous method for monitoring PMN migration in vitro. Prior methods have not used native epithelium, whole basement membrane, or collagenous stroma. PMN penetration of these barriers occurs in the normal inflammatory response and probably involves biochemical mechanisms not required for simple migration through the pores of an artificial filter. The amnion system can be useful for future biochemical and morphological studies of PMN penetration of these barriers and possible repair processes that may follow.